Design of an Off-Grid Solar Power System for a Residential-Scale 1300 VA Application - Yaman, .; Reza, Maulana; Muhammad, Basyir (INTI International University, 2025)
This study presents the design and simulation of an off-grid solar power system optimized for a 1300 VA residential application in Keude Geudong Village, North Aceh, Indonesia. Motivated by the global reliance on non-renewable energy sources, this research aims to offer a sustainable and autonomous energy solution for rural households. The methodology includes detailed energy load auditing, component selection, and system performance simulation using PVSyst software. The system is configured to supply 3.5 kWh of energy per day, utilizing twelve 100 Wp monocrystalline solar panels, a 45 A MPPT charge controller, a 2000 W inverter, and six 52 Ah lithium-ion batteries, ensuring operation for up to three days without additional power input. Simulation results indicate a performance ratio of 58% and a solar fraction of 1:1, confirming the system’s capability to operate independently from the national grid. The proposed configuration demonstrates the technical and practical feasibility of residential solar electrification in rural Indonesian settings. This study offers a fully autonomous home solar solution based on actual energy usage data and site-specific solar information, unlike previous research that focused on large-scale or hybrid systems, providing a scalable model for expanding energy access in off-grid areas.